2014
DOI: 10.1007/s00384-014-1935-6
|View full text |Cite
|
Sign up to set email alerts
|

Perianal disease is associated with psychiatric co-morbidity in Crohn’s disease in remission

Abstract: Anxiety is a frequent, often untreated, condition in patient affected by Crohn's disease in clinical remission. Female sex, history of perianal disease and perianal surgery are major risk factors for anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 34 publications
3
30
0
Order By: Relevance
“…Our study confirmed that psychiatric comorbidity is a frequent condition in CD patients even in those in clinical remission, confirming previous data [ 5 ] and that depressed CD patients have altered coping strategies.…”
Section: Discussionsupporting
confidence: 92%
“…Our study confirmed that psychiatric comorbidity is a frequent condition in CD patients even in those in clinical remission, confirming previous data [ 5 ] and that depressed CD patients have altered coping strategies.…”
Section: Discussionsupporting
confidence: 92%
“…The pCD patients had higher levels of anxiety, stress and depression, in accordance with the literature [12,13,34,35]. Stress and depression may be associated with immunological changes (infiltration of T and B cells, impaired healing, altered levels of defensins) as well as microbiological and genetic factors, all described in the genesis of perianal fistulas [36-38].…”
Section: Discussionsupporting
confidence: 83%
“…However, gender does appear to be linked to differences in psychosocial manifestations of the Psychological illness and inflammatory bowel disease disease. The majority of studies indicate that female gender is a predictor of anxiety and depression in IBD (32,72,76). Females are also believed to be more susceptible to the impact of IBD on HRQOL (77) potentially due to increased symptom perception in women (78).…”
Section: Factors Influencing Anxiety and Depression In Ibdmentioning
confidence: 99%